On the prospects of small and medium-sized manufacturing businesses in Russia - I. N. Ivanov; L. V. Orlova; G. M. Sundukova (Вестник университета)
The sanctions imposed on the Russian Federation (hereinafter referred to  as  RF, Russia) have most significantly affected high-tech sectors of   the economy. In   these conditions, it   is necessary to   solve a   number of  problems, including import substitution, the transition to   the Industry 4.0 concept and low-carbon production and consumption. The need of   participation in   solving these problems is   substantiated not only for large, but also for small and medium-sized businesses (hereinafter referred to   as SMB). The current state and prospects for the development of   small and medium-sized enterprises (hereinafter referred to   as SME) in   Russia are analysed. The article emphasises the discrepancy between the modern state of   the domestic SME and its potential capabilities , in   particular the insufficient participation of  this business in  production activities. The problems of   SMB and its risks related to   the current geopolitical situation are indicated. Ways of   overcoming similar problems in   other countries experiencing sanctions pressure, as   well as  the efforts of   the RF   to   minimise losses of   the Russian SMB, are shown. It   is noted that the implementation of   the national project “Small and medium-sized entrepreneurship and support for individual entrepreneurial initiative” does not solve all the problems of  the SME. As  promising areas for the SMB development, it  is proposed to   strengthen its cooperation with big business, modify the “Grow a   Supplier” programme, and intensify work on  targeted training of   personnel for subjects of   small and medium-sized manufacturing entrepreneurship in   the country’s universities with participation of   the big business. The ways to   ensure the sustainability of   the domestic manufacturing business, possible in   modern conditions, are considered.